STANCE AND CULTURE: A COMPARATIVE STUDY OF ENGLISH AND PERSIAN AUTHORIAL STANCE IN APPLIED LINGUISTICS RESEARCH ARTICLES - Mohammad Reza Hashemi; Hosna Hosseini (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
This study tended to investigate the effect of culture, as depicted in language, on the use of stance in the applied linguistics research articles of two groups: native speakers of Persian, and native speakers of English. The two corpora comprising the discussion sections of forty research articles from reliable journals were compared for amounts and types of stance. In order to find the cultural differences between native Persian and English researchers, the subtypes of stance devices adapted from Hyland's (2005b) model were used. Results showed that the groups used stance markers differently; more specifically, they employed hedges, boosters, attitude markers, and self-mentions differently. Furthermore, culture affects stance features as the meta-discourse devices employed by the researchers in writing the research article genre. The findings have implications for EFL learners and novice non-native writers to know the conventions and patterns as thinking devices for effective writing in academic communities of articles.